Developing PBL-based Student Worksheet to Foster Mathematical Literacy in Probability Topic - Rofidah, Faizatur; Istihapsari, Vita (International Journal on Emerging Mathematics Education, 2024)
The mathematical literacy ability of students in Indonesia is still relatively low, especially at the Vocational High School (SMK) level. One solution that can be implemented is the development of learning media in the form of Student Worksheets (LKPD) based on mathematical literacy using the Problem-Based Learning (PBL) model. This study aims to develop and test the validity and practicality of mathematical literacy-based LKPD on the topic of compound probability events. Using the Research and Development (R&D) method and the ADDIE development model, which consists of five stages—Analysis, Design, Development, Implementation, and Evaluation—this research was conducted on 11th-grade students of the Automotive Engineering 4 class at SMK Negeri 3 Yogyakarta. The results show that the developed LKPD was rated as highly valid by subject matter experts (88.13%) and media experts (92.97%). Additionally, students' responses to the practicality of the LKPD reached 93.65%, which falls into the highly practical category. Thus, this LKPD can be used as an effective learning medium to improve the mathematical literacy of vocational high school students.